Measuring glare induced visual fatigue by fixation disparity variation. - Glimne, S.; Seimyr, G. Öqvist; Ygge, J.; Nylén, P.; Brautaset, R.L. (Work, 2013)
OBJECTIVE: To introduce fixation disparity variance as an objective measure of visual discomfort. A higher variance in fixation disparity is indicative of more visual fatigue. This observation is based on the results from a study where we investigated how fixation disparity was affected by glare on a VDU. Participants. In total 16 subjects with normal vision participated in this study. METHOD: In a balanced repeated-measurement experiment, all subjects performed equal near-vision tasks. In addition to the condition of no glare three controlled conditions of glare were used: direct light, indirect light, and desk luminary. After each condition, the fixation disparity was measured 15 times using a computerized fixation disparity test. RESULTS: The results showed that the average (mean) disparity was found to increase towards esophoric (crossed) with the adversity of the lighting conditions, but the differences were not significant. However, when analyzing the variation (standard deviation) within the 15 measurements and comparing these between conditions, we found that the direct light condition resulted in significantly higher variation compared to lighting condition of no glare and desk luminary lighting. CONCLUSION: Based on these findings, we argue that fixation disparity variance may be a useful objective measure of visual fatigue.